2004
DOI: 10.1128/aac.48.3.780-782.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early Bactericidal Activity of Moxifloxacin in Treatment of Pulmonary Tuberculosis: a Prospective, Randomized Study

Abstract: Moxifloxacin is the most active fluoroquinolone against Mycobacterium tuberculosis in vitro. However, data about the efficacy in patients are not available. We enrolled 17 patients with tuberculosis in a prospective, randomized study. After 5 days of monotherapy with either moxifloxacin or isoniazid, we detected significant decreases in mean CFU per milliliter in sputum in both groups. The calculated early bactericidal activities for isoniazid and moxifloxacin were 0.209 and 0.273 log 10 CFU per ml of sputum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 10 publications
(13 reference statements)
6
72
0
4
Order By: Relevance
“…Drug Resistance 103 (Takiff et al, 1994;Pletz et al, 2004;Rattan et al, 1998;Ginsburg et al, 2003;Cheng et al, 2004) Aminoglycosides Kanamycin Amikacin Takiff et al, 1994;Taniguchi et al, 1997;Suzuki et al, 1998;Ramaswamy et al, 2004;Vannelli et al, 2002) Ethionamide Taniguchi et al, 1997;Suzuki et al, 1995) a) Minimum inhibitory concentration. b) Polymerase chain reaction-single strand conformation polymorphism.…”
Section: Molecular Methods To Predict Drug Resistancementioning
confidence: 99%
“…Drug Resistance 103 (Takiff et al, 1994;Pletz et al, 2004;Rattan et al, 1998;Ginsburg et al, 2003;Cheng et al, 2004) Aminoglycosides Kanamycin Amikacin Takiff et al, 1994;Taniguchi et al, 1997;Suzuki et al, 1998;Ramaswamy et al, 2004;Vannelli et al, 2002) Ethionamide Taniguchi et al, 1997;Suzuki et al, 1995) a) Minimum inhibitory concentration. b) Polymerase chain reaction-single strand conformation polymorphism.…”
Section: Molecular Methods To Predict Drug Resistancementioning
confidence: 99%
“…Moxifloxacin efficacy has also been shown in humans. Early bactericidal activity (EBA) studies in newly diagnosed pulmonary TB patients showed comparable activity of moxifloxacin (400mg) and isoniazid (300mg or 6mg/kg) (Pletz et al, 2004). The regimen with moxifloxacin caused the fastest decrease in CFU during the early phase of a biexponential fall (in a nonlinear model that differentiates between quickly and slowly eliminated bacilli) (Rustomjee et al, 2008b).…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 99%
“…It exhibits MIC of 0.5 g/mL against Mtb (Shandil et al, 2007). It displayed early bactericidal activity comparable to INH and rifampin in humans (Pletz 2004;Gosling 2003). It affects bacteria by binding to the DNA gyrase and topisomerase IV, which are involved in bacterial replication.…”
Section: Fluoroquinolonesmentioning
confidence: 99%